Prevalência da infecção por Neisseria gonorrhoeae em adolescentes do sexo feminino no município de Goiânia, Goiás - DUARTE, Jannaína Karlla de Queiroz (2008)
BACKGROUND: Adolescents are at great risk for genital Neisseria gonorrhoeae infection. Although most infections are asymptomatic it can cause severe reproductive sequels to women. Few studies exist about prevalence of these infection in Brazil and fewer in adolescent population. OBJECTIVES: To determine the prevalence of Neisseria gonorrhoeae genital infection among female sexually active adolescents, in Distrito Sanitário Noroeste from Goiânia, Brazil and to identify demographic and behavioral profiles associated to gonococcal infection. METHODS: We performed a cross-sectional study among 427 sexually active female adolescents (15-19 years), random selected at Distrito Sanitário Noroeste and served by the Health Family Program. It were excluded pregnant adolescents, pos-partum, using antibiotics or on period. The gonococcal infection was determined by using polimerase chain reaction (PCR) of Amplicor Roche kit for N. gonorrhoeae and C. trachomatis applied to endocervical swab specimens. Sociodemographic and behavioral data were assessed by face-to-face questionnaire. RESULTS: The mean age of 427 random selected adolescents was 17.2 ± 1.3 years, most female were single (67.9%). The mean age of menarch was 12.4 years and at first sexual intercourse was 15 years. 35,1% had the first sexual intercourse before 15 years and 16,2% reported more than 3 partners in life. About 80% of the participants reported inconsistent condom use. Among those with gonococcal infection, 22,2% also had chlamydial infection. The prevalence of gonococcal infection was 2,1% (95% CI 1,0 4,1). CONCLUSIONS: Adolescents studied presented risk sexual behaviors to sexually transmitted diseases. These results demonstrate the need for preventive medicine programs for adolescents females with ongoing STI prevention activities.